Modelagem matemática da Dinâmica de Fluxo Riacho-Aquífero na Microbacia Hidrográfica do riacho São José na região do Cariri Cearense - Fontenele, Sávio de Brito (2010)
It relates the understanding of the flow dynamics between the São José stream and Rio da Batateira aquifer, located in the Cariri region in Ceará. The stream discharges were monitored by the chemical tracer method, which obtained a good linear correlation with the Parshall flume. According to the SCS-CN method, there was no runoff in the days prior to flow measurement, indicating that the increase in flow during the rainy season corresponds to changes in the pattern of subsurface flow and base-flow of the stream. The average hydraulic conductivity of the aquifer, estimated at 1.69 x10-5 m s-1, was obtained from geostatistics, using the technique of kriging. The specific production of the aquifer (5%) and the conductance of the stream bed (16,800 m² dia-1) were obtained in the stream-aquifer flow model calibration flow by using the MODFLOW application. In the steady state calibration we obtained the annual recharge of 45 mm and in the transient state it was possible to distribute this recharge into the months of April (16 mm) and May 2009 (29 mm). Recharges occurred only in the months having rainfall exceeding 200 mm. As MODFLOW only simulates the flow in saturated media, the flow rate calculated for the stream corresponds only to the base flow and the excess observed corresponds to the subsurface flow not calculated. The simulation for four scenarios, considering the extreme values of annual rainfall recorded in pluviometers of the region and changes in the recharge area of the river catchment, showed the need for urban planning in the area, aiming at the future control of soil use and occupation with a focus on preservation of groundwater and surface water resources.